A review of the bioactivity of coffee, caffeine and key coffee constituents on inflammatory responses linked to depression. (October 2015) - Hall, Susan; Desbrow, Ben; Anoopkumar-Dukie, Shailendra; Davey, Andrew K.; Arora, Devinder; McDermott, Catherine; Schubert, Matthew M.; Perkins, Anthony V.; Kiefel, Milton J.; Grant, Gary D.
Abstract: Coffee is a widely consumed beverage containing numerous biologically active constituents predominantly belonging to the polyphenol and alkaloid classes. It has been established that coffee has a beneficial effect on numerous disease states including depression. A number of prospective and retrospective cohort studies have assessed the effects of coffee consumption on the relative risk of developing major depressive disorder in humans. These studies have identified an inverse relationship between the consumption of caffeinated coffee and the risk of developing depression. Caffeine, chlorogenic acid, ferulic acid and caffeic acid, all important constituents of coffee, have been shown to possess biological activities that highlight a possible mechanistic link to the pathology of depression. This review aims to assess the evidence from the biological evaluation of these constituents of coffee on markers of inflammation associated with depression in in vitro and in vivo models of inflammation, neuroinflammation and depression. The ability of bioactive coffee constituents to modulate the parameters of neuroinflammation has been shown with caffeine having strong antioxidant properties in vitro, chlorogenic acid and caffeic acid having strong anti-inflammatory and antioxidant properties in vitro and ferulic acid having activities in in vivo animal models of depression. Highlights: Coffee has been shown to have beneficial effects in numerous disease states including depression Epidemiological studies have shown an inverse correlation between the consumption of coffee and the incidence of depression. A number of bioactive constituents of coffee have possible mechanistic links to modulating biomarkers of depression.